The Phenomenon of Commercial Sex Workers in Clubs and Karaoke (Study in Semarang City) - Saragih, Rotua Octaviyani; Bangun, Michael Hagana; Simanjuntak, Jane Baiduri; Damanik, Kezia; Astriana, Yuni (Law Research Review Quarterly, 2019)
Prostitution is a disease of society / social deviations carried out in an organized manner consisting of pimps, Commercial Sex Workers (CSWs), and masher men. Criminal law rules in the Criminal Code (KUHP) only regulates pimps, not yet regulating commercial sex workers. The absence of rules regarding prostitutes and masher men in positive law in Indonesia has resulted in the practice of prostitution remaining in the midst of social life. Not only that, with the existence of commercial sex workers who can arbitrarily work wherever they want, it will certainly cause unrest in the surrounding community. Of course this can interfere with the ongoing life in the environment. The research objective is to find out how the background of the CSWs finally decides for workers as CSWs and also each process to get to the stage of working with these CSWs. This study uses a qualitative approach and interview methods for the approach. A qualitative approach conducts research on research that is descriptive in nature and tends to use analysis. The process and meaning are more highlighted in qualitative research. The theoretical foundation is used as a guide so that the focus of research is in accordance with the facts in the field. After conducting research at Karaoke & Discotheque in Semarang City, conducted secret interviews with CSWs who worked there.